A pluriliteracies approach to content and language integrated learning - mapping learner progressions in knowledge construction and meaning-making - Meyer, Oliver; Coyle, Do; Halbach, Ana; Schuck, Kevin; Ting, Teresa (Language, culture, and curriculum, 2015)
Over the past decades content and language integrated learning (CLIL) research has predominantly focused on the language proficiency of CLIL learners. The results are very promising and show that working language skills in learners, especially reading and listening skills, can be improved through a CLIL programme. Studies focusing on subject learners are still few but they indicate that learners maintain or under certain conditions can improve their subject learning when compared to learners learning in L1. However, more recent studies have raised challenging questions concerning academic language competence which indicate that CLIL instruction may not be reaching its full potential. Unravelling the integrated approach and the inherent interrelationship of using language for progressing knowledge construction and meaning-making needs to be addressed, drawing together linguistic and pedagogic theoretical underpinnings. This article posits that CLIL can pragmatically address the growing educational malaise of functional illiteracy. We reason that progression along the knowledge pathway towards deeper subject understanding requires a greater command of secondary discourse, and mastery of subject-specific literacies. In traditional classrooms, content teachers do not usually focus on the quality of learners' disciplinary literacy and discourse. In language classrooms, subject-specific literacies are considered irrelevant. We suggest that if 'literacy' were at the centre of the learning agenda, regardless of subject disciplines, a fundamental shift towards deeper learning would occur. Therefore, the article addresses two fundamental issues: (i) the role of subject-specific or disciplinary literacies in CLIL and (ii) the iteration of a model building on the existing 4Cs framework, which maps literacy and language progression in CLIL contexts and serves as a guide for evolving classroom practices.